Metformin promotes innate immunity through a conserved PMK-1/p38 MAPK pathway. Issue 1 (1st January 2020) - Xiao, Yi; Liu, Fang; Li, Sanhua; Jiang, Nian; Yu, Changyan; Zhu, Xinting; Qin, Ying; Hui, Jing; Meng, Lingjie; Song, Changwei; Li, Xiao-Fei; Liu, Yun
ABSTRACT: Metformin, as the first-line oral drug for type 2 diabetes, has proven benefits against aging, cancer and cardiovascular diseases. But the influence of metformin to the immune response and its molecular mechanisms remain obscure. Metformin increases resistance to not only the Gram-negative pathogens Pseudomonas aeruginosa and Salmonella enterica but also the Gram-positive pathogens Enterococcus faecalis and Staphylococcus aureus . Meanwhile, metformin protects the animals from the infection by enhancing the tolerance to the pathogen infection rather than by reducing the bacterial burden. Through the screening of classical immune pathways in C. elegans, we find metformin enhances innate immunity through p38 MAPK pathway. Furthermore, activated p38/PMK-1 by metformin acts on the intestine for innate immune response. In addition, metformin-treated mice have increased resistance to P. aeruginosa PA14 infection and significantly increased the levels of active PMK-1. Therefore, promoted p38/PMK-1-mediated innate immunity by metformin is conserved from worms to mammals. Our work provides a conserved mechanism by which metformin enhances immune response and boosts its therapeutic application in the treatment of pathogen infection.